2016
DOI: 10.1007/s40069-016-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure of Calcium Sulfoaluminate Paste and Durability of Concrete in Freeze–Thaw Environment

Abstract: Mercury intrusion and nitrogen sorption porosimetry were employed to investigate the pore structure of calcium sulfoaluminate (CSA) and portland cement pastes with cement-to-water ratio (w/c) of 0.40, 0.50, and 0.60. A unimodal distribution of pore size was drawn for CSA cement pastes, whereas a bimodal distribution was established for the portland cement pastes through analysis of mercury intrusion porosimetry. For the experimental results generated by nitrogen sorption porosimetry, the CSA cement pastes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In previous studies, most of the literature has focused on the variation of macroscopic mechanical properties of concrete under the condition of freeze–thaws cycles. In fact, the microscopic pore structure and pore size distribution inside concrete are closely related to the macroscopic mechanical properties and durability [ 23 , 24 , 44 ]. Therefore, it is necessary to establish a damage variable based on pore structure to describe the evolution of mechanical properties of concrete under different freeze–thaw cycling conditions.…”
Section: Microstructure Characterization Based On Nmr Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, most of the literature has focused on the variation of macroscopic mechanical properties of concrete under the condition of freeze–thaws cycles. In fact, the microscopic pore structure and pore size distribution inside concrete are closely related to the macroscopic mechanical properties and durability [ 23 , 24 , 44 ]. Therefore, it is necessary to establish a damage variable based on pore structure to describe the evolution of mechanical properties of concrete under different freeze–thaw cycling conditions.…”
Section: Microstructure Characterization Based On Nmr Porositymentioning
confidence: 99%
“…The porosity and pore size distribution (PSD) are significant parameters of the pore structure, which directly affect the permeability, mechanical properties, and durability of concrete [ 21 , 22 , 23 ]. Kashif et al [ 24 , 25 ] concluded that the incorporation of 0.03% graphene oxide (GO) can significantly improve all mechanical properties and reduce microcracks or porosity of the cement composites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, CSA-based concrete can perform at a temperature of under 5 °C [88]. CSA-based concrete is a good anti-freeze material, where under freeze-thaw performance testing, CSA repair material was found to have 12% less weight loss compared to OPC concrete [89]. Also, CSA-based concrete exhibits good resistance to corrosion and chemical attacks such as sulphate, magnesium, and ammonium salts [81,90].…”
Section: Calcium Sulphoaluminate-basedmentioning
confidence: 99%
“…It is widely acknowledged that CSA concrete exhibits superior performance in freeze-thaw environments compared to OPC concrete owing to its lower porosity and the inclusion of more coarse pores [ 21 , 22 ]. It has also been posited that CSA concrete is more resistant to sulfate attack due primarily to the major hydration product, i.e., ettringite does not react with sulfate [ 9 , 23 ].…”
Section: Introductionmentioning
confidence: 99%